2020
DOI: 10.3389/fsufs.2020.543587
|View full text |Cite
|
Sign up to set email alerts
|

Pasture-Based Dairy Systems in Temperate Lowlands: Challenges and Opportunities for the Future

Abstract: Improved efficiency in dairy systems is a significant challenge for the future, to meet increased food demand while competing for inputs, adapting to climate change, and delivering ecosystem services. Future grazing systems can play a major role to supply healthier foods within systems with a reduced reliance on fossil fuels and chemical inputs, while also delivering environmental, biodiversity, and animal welfare benefits. Can we design lower-input systems that deliver efficient levels of output in a positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 55 publications
(52 reference statements)
0
12
0
Order By: Relevance
“…Pastures are multifunctional areas as they provide goods and ecosystem services, such as the maintenance of biodiversity, feed and shelter to animals [6]. However, several Monthly rain played significant positive roles on the concentrations of five nutritive parameters-namely, CP, Ash, DMD, OMD and EE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pastures are multifunctional areas as they provide goods and ecosystem services, such as the maintenance of biodiversity, feed and shelter to animals [6]. However, several Monthly rain played significant positive roles on the concentrations of five nutritive parameters-namely, CP, Ash, DMD, OMD and EE.…”
Section: Discussionmentioning
confidence: 99%
“…Pastures are multifunctional areas as they provide goods and ecosystem services, such as the maintenance of biodiversity, feed and shelter to animals [6]. However, several factors contribute towards the quality, quantity and reliability of pasture production, and these include species [40], plant part, stage of maturity [41], soil type [42], altitude [43] and climatic variables [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a North American study, Belflower et al (2012) reported that a confined dairy had more than twice the per cow milk production of a pasture-based dairy (roughly 11,000 kg cow -1 y -1 vs. roughly 5,000 kg cow -1 y -1 ). As described by Delaby et al (2020), the high genetic potential for milk production of Holstein cows are unable to meet their potential in a grazing system without feed supplementation. This lower production rate is also observed in African and New Zealand dairies, many of which adopt a lower-input, lower-production farming strategy (Nacer et al, 2016;Podstolski, 2016).…”
Section: Farm Design and Managementmentioning
confidence: 99%
“…The design of a grass-based model within global dairy production systems is indeed peculiar due to its high dependence on natural forces (such as climate) for the production of perishable feed, and grazing animals for the autonomous management of feed quality and utilization (Delaby and Horan, 2017). It is widely acknowledged that the overall integrity of this model of milk production is based on high productivity grassland management in combination with genetically elite animal genotypes capable of compact seasonal calving while efficiently converting grazed grass to milk fat and protein (milk solids; MS) (O'Sullivan et al, 2019ba;Delaby et al, 2020). Within such systems, opportunities to increase animal feed efficiency are limited and the amount of milk produced from a given amount of feed is a key measure of both the efficiency and environmental impact of the system (Grainger and Beauchemin, 2011).…”
Section: Introductionmentioning
confidence: 99%